2017
DOI: 10.1111/cbdd.13153
|View full text |Cite
|
Sign up to set email alerts
|

Octyl ester of ginsenoside compound K as novel anti‐hepatoma compound: Synthesis and evaluation on murine H22 cells in vitro and in vivo

Abstract: Ginsenoside compound K (M1) is the active form of major ginsenosides deglycosylated by intestinal bacteria after oral administration. However, M1 was reported to selectively accumulate in liver and transform to fatty acid esters. Ester of M1 was not excreted by bile as M1 was, which means it was accumulated in the liver longer than M1. This study reported a synthetic method of M1-O, a mono-octyl ester of M1, and evaluated the anticancer property against murine H22 cell both in vitro and in vivo. As a result, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Wound healing is a highly complex process, with many critical factors influencing normal wound recovery and impaired wound healing caused severe consequences, even death 24 . With the increase in chronic wounds due to accidents, aging populations, and incidences of diseases such as diabetes, wound healing continues to be a considerable challenge in clinical treatment 14 . Although several drugs reportedly promote wound healing, including vascular endothelial growth factor (VEGF) and erythropoietin (EPO), they have yet not to achieve ideal effects 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wound healing is a highly complex process, with many critical factors influencing normal wound recovery and impaired wound healing caused severe consequences, even death 24 . With the increase in chronic wounds due to accidents, aging populations, and incidences of diseases such as diabetes, wound healing continues to be a considerable challenge in clinical treatment 14 . Although several drugs reportedly promote wound healing, including vascular endothelial growth factor (VEGF) and erythropoietin (EPO), they have yet not to achieve ideal effects 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying novel molecules for the treatment of wounds is still of great necessity. Compared with traditional drugs, peptides exhibit many advantages such as high activity, specificity, and stability, and have thus provoked considerable scientific attention worldwide 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ginsenoside compound K, the active form of major ginsenosides deglycosylated by intestinal bacteria after oral administration, was found to selectively accumulate in the liver and transform to mono-octyl ester derivatives. Study on its potential metabolite (m1- O ) showed that m1- O could induce apoptosis of H22 tumor cells and alleviate the atrophy of immune organs compared with the chemotherapy drug, cyclophosphamide [19].…”
Section: Introductionmentioning
confidence: 99%